(untitled) (CAHIERS MAGELLANES-NS, 2024)
An in vitro study to compare the adaptation of denture bases fabricated with 2 different techniques (CAD-CAM 3D Printed & Conventional Heat-Cured), Before Relining, After Relining with Hard & Soft liners & After Thermal-Cycling. Material and Methods: maxillary edentulous definitive casts were prepared from an edentulous silicon mold that fabricated with morphology closely resembling an American College of Prosthodontists, Type A classification of residual ridge morphology. Dental stone type IV was mixed at a ratio of 25 ml of water to 100 gm of powder. A three-dimensional image for the stone model was taken by (3Shape laboratory scanner, Denmark) scanning was accomplished with (6 µm) accuracy according to ISO (12836). The next step was the Lazer production of (60) metal casts by using the STL file with machine (RITON, Procured Company, China). After fabrication of 60 record base the digital superimposing with the best fit by EXOCAD was done and measuring the gap in 10 points in which it distributed over the whole anatomical landmark. (A, B, C, D, E, F, G, H, K&L) The 10 points were distributed randomly on the whole anatomical landmarks area on the cast. The cast was divided into five major areas evaluated in the five functional areas, namely, posterior palatal seal, anterior border seal, crest of the ridge, maxillary tuberosity, and palatal area. 20 specimens were tested before relining, 10 were CAD-CAM 3D Printed & 10 were Conventional Heat cured (control), 40 specimens of adaptation test were divided into two main groups, 3D printed group 20 specimens & conventional group 20 specimens, each group subdivided into another two subgroup, 3D samples from (1-10), they were hard relined with PMMA (PROCRYLA, Germany). 3D samples from (11-20), they were soft relined with resilient material (SUPER SOFT, USA). conventional denture base material samples from (1-10), they were hard relined with PMMA, conventional denture base material samples from (11-20), they were soft relined with resilient material then they were tested. The specimens were kept for 24 hours in an incubator at 37℃ and not thermocycled, then they were thermocycled for a total of 5000 cycles between 5 ℃ and 55 ℃ with a dwell time of 60 seconds and a transfer time of 30 seconds. subjected to 5,000 cycles of thermocycling (SD Mechatronik Thermocycler; SD Mechatronik GmbH, Westerham, Germany) then they were tested again Figure (11). Results: (⸸): t-test (Two independent sample), (¥): Z=Mann-Whitney U were used to compare the mean values of Adaptation Before Relining: 3D Printed vs. Conventional denture base materials, Adaptation: Conventional significantly higher than 3D Printed (p<0.01). £: F-test One Way ANOVA, Ӄ: Kruskal-Wallis H test, (a),(b),(c) multiple comparison by Duncan multiple range test for Parametric test, (1),(2),(3),(4) Rank for Not Parametric test, were used for Comparison Analysis of Adaptation of 3D & conventional Denture Bases between 3DH (3D Hard), 3DS (3D Soft), CH (Conventional Hard), & CS (Conventional Soft) liners at Both Group after relining, Adaptation: Significant differences(p<0.05), highest in (3DS), lowest in (CH). After Thermal-Cycling the results were; Adaptation: Significant differences (p<0.05) highest in (3DS), lowest in (CH). Conclusion: Adaptation of the CAD-CAM 3D Printed denture Base was lower than Conventional heat-cured before Relining. Adaptation of the CAD-CAM 3D Printed denture Base After Relining with hard & soft liners were increased significantly, but decreased slightly After Thermal-Cycling. 3D soft was the best adaptable denture base & the Conventional hard was with the lowest adaptable denture base.